Cavo - Supra - Hepatic Lesions by Enclosed Traumatism: about a case - Crestanello, Francisco; Rompani, Omar; Gastambide, Carmelo; Díaz, Ariel (Cirugía del Uruguay, 1980)
Report on one case of blunt hepatic traumatism, with lesion of pastero - superior area of right lobe and divulsion of rig:ht suprahepatic and severa! accessor)" suprahepatics of the cava. The patient was successfully operated by atypical hepatectomy of segments 7 and 8.